PEMANFAATAN APLIKASI KAHOOT! SEBAGAI DIGITAL GAME BASED LEARNING PADA MATA PELAJARAN FIQH DI SMP NEGERI 6 SINGOSARI MALANG - Rahmad Yoga Nugroho; Qurroti A'yun; Atika Zuhrotus Sufiyana (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The importance of learning media used in the learning process makes a lot of innovations in terms of learning media that can be used by teachers. One of the learning media used by teachers at SMP Negeri 6 Singosari Malang is Kahoot! This study aims to determine the effect and level of student learning outcomes in using the Kahoot! As a digital game based learning on Fiqh subjects. The method used in this research is quantitative research with quasi-experimental research type. The results of this study are the use of the pre-test and post-test design group learning models have differences between the control and experimental classes so that significant results are obtained, namely 0.000.